Are attitudes and intentions towards sex associated with risky sexual behaviour in urban Western Australian adolescents? - Hendriks, Jacqueline (Curtin University, 2014)
A survey dataset of 1616 heterosexual West Australian adolescents was used to create three psychometric scales, through application of the Rasch Unidimensional Measurement Model. Attitudes towards abortion, adolescent parenthood and contraception were each associated with sexual behaviours linked to an increased risk of unwanted pregnancy or sexually transmissible infection. The relative importance of various biopsychosocial factors in relation to attitude formation was established. Overall findings support interventions focusing on the formation of positive contraceptive attitudes.